REPRESENTATION OF GASTRONOMY BRANDINGTHROUGH “ARUNA AND HER PALATE” FILM - Altamira, Melisa Bunga (UI Scholars Hub, 2022)
Indonesia is one of the well-known international tourist destinations, one of which is through its culinary diversity. The variety of culinary culture in Indonesia cannot be separated from the historical stories and characteristics of each region. With these peculiarities, Indonesian cuisine must of course receive special attention in the promotion process. In the world of culinary marketing, there is a concept known as gastronomy branding. This concept briefly means doing marketing communication activities about food. Mass media, especially films, can be a channel for mass communication to carry out this gastronomy branding activity. Through its reach, films can convey a gastronomy branding communication message to introduce Indonesian cuisine to a wide audience, both nationally and internationally. One of the Indonesian films that raises the culinary specialties of the archipelago is